Multinuclear metal-organic coordination structures containing metal-cluster nodes studied by scanning tunneling microscopy - Yansong Wang; Xin Li; Qianxi Yang; Qian Shen; Yang He; Yajie Zhang; Yongfeng Wang (Fundamental Research, 2025)
Embedding metal clusters in surface-supported metal-organic frameworks gives rise to multinuclear metal-organic coordination structures (MMOCs). The controllable configurations, exposed clusters, and multilevel interactions of MMOCs imply numerous potential applications, such as in catalysis, light-energy conversion, spintronics, and molecular electronics. Thus, the fabrication of MMOCs has been investigated extensively. According to the formation mechanism of metal clusters, we summarize five types of MMOCs. Attractive properties, e.g., magnetism, charge transfer and chirality, emerge in these systems. The surface-supported feature enables researchers to detect these properties via surface-sensitive techniques, such as scanning tunneling microscopy/spectroscopy, X-ray photoelectron spectroscopy, noncontact atomic force microscopy and local contact potential difference measurement. In addition, the results obtained from density functional theory calculations can be mutually verified with experiments. These studies pave the way for further applications of MMOCs.